2009
DOI: 10.1002/mds.22535
|View full text |Cite
|
Sign up to set email alerts
|

Effect of movement frequency on repetitive finger movements in patients with Parkinson's disease

Abstract: Performance of repetitive hand movements in patients with Parkinson's disease (PD) is characterized by slowness, reduced movement amplitude, and hesitation or arrests in ongoing movement. Currently, the factors and mechanisms contributing to impaired performance of these types of movement remain poorly understood. This study examined the effects of movement frequency and medication on the performance of unconstrained index finger flexion movements in patients with PD and matched control subjects. Movements wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 28 publications
7
64
1
1
Order By: Relevance
“…There is evidence that medication itself may have a differential effect on movement rate and amplitude, as demonstrated by past research (Espay et al, 2009, 2010, 2011; Stegemöller et al, 2009; Teo et al, 2013, 2014). In the current study, we believed that medication did not play a major role influencing the outcomes for PD patients.…”
Section: Discussionmentioning
confidence: 69%
“…There is evidence that medication itself may have a differential effect on movement rate and amplitude, as demonstrated by past research (Espay et al, 2009, 2010, 2011; Stegemöller et al, 2009; Teo et al, 2013, 2014). In the current study, we believed that medication did not play a major role influencing the outcomes for PD patients.…”
Section: Discussionmentioning
confidence: 69%
“…When patients perform the task at high movement rates, the impairment is markedly worse than when it is performed at low rates. Quantitative studies have shown that deterioration of repetitive movement performance occurs when movement rate nears 2 Hz and above [18, 20, 28] and is characterized by a marked increase in movement rate, reduced movement amplitude, and increased variance in phase and inter-movement interval [6, 18, 20, 28]. These changes in performance are considered to reflect a disordered supraspinal drive to muscles due to dysfunction of the basal ganglia.…”
mentioning
confidence: 99%
“…EEG were obtained from a series of finger tapping experiments using an acoustic pacing tone at a rate of 2 Hz from a non-impaired adult as part of a study examining the effects of movement frequency on movement performance and movement-related cortical oscillations in people with Parkinson’s disease (Stegemöller et al, 2009). Data were acquired with a Neuroscan SynAmps system, band-pass filtered (DC to 250 Hz), sampling rate 1000 Hz (subsequently downsampled to 250 Hz), and digitised with a 16-bit analogue-to-digital converter.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies have examined movement-related oscillations in the context of single discrete movements, yet marked impairments are often seen during the performance of repetitive motor behaviours such as finger tapping and locomotion. It has recently shown that repetitive finger movements are severely impaired in people with Parkinson’s disease, but this impairment is movement frequency dependent (Stegemöller et al, 2009). In light of evidence that pharmacological and surgical treatments of movement disorders can have a differential effect on movement-related oscillations in the α-and β-bands (Brown and Marsden, 1999), there is considerable need for analysis methods that can resolve the movement-related oscillations simultaneously in both the frequency and time domains during repetitive motor behaviours.…”
Section: Introductionmentioning
confidence: 99%